(untitled) (Research, Society and Development, 2022)
Given that the COVID-19 pandemic has brought about a major problem in world health, it has led to a greater performance of health professionals, including pharmacists, due to the high demand in the provision of health services in an individualized and collective way in pharmacotherapy and health education. SARS-CoV-2 is contagious, manifesting itself in a severe acute form, characterized as severe acute respiratory syndrome (ARDS), where symptoms are similar to other viral infections, with variability of transmissibility from individual to individual. Research is carried out on drug interactions during the pandemic in Açailândia-MA, in order to point out the importance of the clinical pharmacist during the pandemic scenario. Therefore, it is necessary to analyze the drug interactions that are recurrent in the treatment of COVID-19 and compile the problem of self-medication during the pandemic. Field research is carried out using medical prescriptions. In view of this, it appears that the results presented from 248 medical prescriptions result in antimicrobials (n=280), antiparasitics (n=138) and vitamins (n=128) prescribed, observing their interactions by severity, highlighting moderate in 96, 3% in higher percentage. What imposes the observation is that the pharmacist becomes the essential professional in the quality of life of the patient, being able to optimize the pharmacological treatment and improve health and adherence to pharmacotherapy.